2013
DOI: 10.1590/s0004-27302013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Final height in congenital adrenal hyperplasia: the dilemma of hypercortisolism versus hyperandrogenism

Abstract: Objective: The purpose of this study was to identify factors that might interfere with reaching the final height in patients with 21-hydroxylase deficiency (21-OHD). Subjects and methods: Thirty-one patients with classical 21-OHD who reached their FH in our Institution were evaluated in order to compare the Z score for final height (FHZ) with: (1) the target height, (2) the standard height for the population, and (3) the hydrocortisone treatment schedule. Results: The FHZ of -2.13 ± 1.11 had a significant nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(34 reference statements)
1
3
1
Order By: Relevance
“…We found glucocorticoid replacement in the studied group was uniform and appropriate, following the current recommendations and consistent with previous findings of therapeutic efficacy in the same group of children (21,22). Follow-up was performed systematically at the same medical facility, and patients had no clinical signs of glucocorticoid excess or suppressed levels of serum steroids.…”
Section: Discussionsupporting
confidence: 87%
“…We found glucocorticoid replacement in the studied group was uniform and appropriate, following the current recommendations and consistent with previous findings of therapeutic efficacy in the same group of children (21,22). Follow-up was performed systematically at the same medical facility, and patients had no clinical signs of glucocorticoid excess or suppressed levels of serum steroids.…”
Section: Discussionsupporting
confidence: 87%
“…Height outcome is related to the dose of corticosteroid, with some authors describing a negative correlation between hydrocortisone doses and FAH [32]. Although we noted that FAH in males on steroid doses ≤ 15 mg/m 2 /day was significantly higher than in those receiving higher doses, we found no correlation between the actual dose of steroids and FAH, suggesting that growth is maintained within this cut-off dose.…”
Section: Discussioncontrasting
confidence: 79%
“…A meta-analysis of 35 studies of classic 21OH deficiency showed an average final height of 1.38 standard deviations below the population norm. 72 Whereas studies reveal an association between higher doses of hydrocortisone and shorter final height, 92,93 earlier rather than later diagnosis and treatment has been associated with improved height outcomes, emphasizing the importance of prevention of hyperandrogenism.…”
Section: Long-term Complicationsmentioning
confidence: 99%